Two new species of Leydigia Kurz, 1875 (Chydoridae, Cladocera) from Spain - Kotov, Alexey A.; Alonso, Miguel (Zootaxa, 2010)
We describe two new species of Leydigia Kurz, 1875 (Chydoridae, Cladocera) from Spain. L. (Neoleydigia) iberica sp. nov. has a series of traits rarely observed in well-studied species of the subgenus L. (Neoleydigia), and never in this combination: (1) PP distance large; (2) numerous, low hillocks on preanal margin of postabdomen; (3) numerous setae in lateral fascicles on postabdomen, plus distalmost and next setae subequal in size; (4) sensory seta shifted to distal end of antenna I, but not so markedly as in L. microps; (5) fully setulated basal segment of distalmost scraper on limb III; (6) 5 setae on exopodite III. L (N.) korovchinskyi sp. nov. has seven setae on limb III exopodite, characteristic for only two species of the subgenus L. (Neoleydigia) Kotov, 2009, namely L. (N.) propinqua and L. (N.) microps, but the former differs from both latter taxa in: (1) absence of a “coarse” striation; (2) rounded apex of labral keel and (3) longer setae 34 of exopodite III. At this moment, each species was found in a single locality. Both species are rare and seem endemic of Iberian Peninsula (but may be found in some surrounded Mediterranean territories); they could be regarded as relicts sensu Korovchinsky (2006).